Analysis of the Incidence and Survival of Gastric Cancer Based on the Lauren Classification: A Large Population-Based Study Using SEER - Tang, Chao-Tao; Zeng, Ling; Yang, Jing; Zeng, Chunyan; Chen, Youxiang (Frontiers in Oncology, 2020)
Abstract Background Limited evidence exists on the incidence of gastric cancer (GC), and contradictory results exist for the prognosis of GC based on the Lauren classification. We analyzed the incidence and survival of GC based on the Lauren classification. Methods The SEER database from 1975 through 2015 was used to identify all patients with surgically resected, histologically diagnosed intestinal or diffused type GC. Propensity score matching was used to analyze the association between the Lauren classification type and prognosis. Results The trend of total GC incidence showed an obvious decrease (APC=-1.51, 95% CI, -2.31- -1.01) as well as that of the intestinal type (APC= -1.43, 95% CI, -2.01- -1.12). However, we found the relative incidence of the diffused type was increased (APC=0.6, 95% CI, 0.41-0.82). The trend of the total incidence of GC (APC= -1.31, 95% CI, -1.91- -1.03) and that of the intestinal type (APC=-1.11, 95% CI, -1.53- -0.98) were decreased in 40-49-year-olds, but that of the diffused type was increased (APC=1.5, 95% CI, 1.2-1.72). We found that trends in GC incidence exhibited a similar pattern in the regional and distant stages and showed a decrease from 1975 through 2015. However, the incidence rate of the local stage was increased, with an APC of 0.5 (95% CI, 0.3-0.7). We identified 15989 GC cases from the SEER database, including 13852 intestinal type and 2138 diffused type cases. The 1336 intestinal type cases were matched with 1336 diffused type cases using propensity score matching (PSM), and patients with the diffused type had a better prognosis than patients with the intestinal type (HR=0.56, 95% CI, 0.45-0.78). However, we found that patients with diffused type GC had worse survival than patients with intestinal type GC in the cohort from Renji Hospital (P<0.001). Conclusion The total incidence of GC and that of the intestinal type GC decreased, but the incidence of diffused type GC increased in 40-49-year-olds. Diffused types of GCs may have a different prognoses compared to intestinal type GCs in different patient cohorts. Nevertheless, these results should be interpreted with caution in assessing the prognosis in combination with other factors.